Polyvinylpyrrolidone and Brij-35 Stabilized IrO2 Nanoclusters As Highly Effective Catalyst In The Degradation Of Acid Orange 10: A Comparative Study - Rajni Lasyal; Shakunj Rajput (Journal of Water and Environmental Nanotechnology)
In this study, the degradation of azo-dye acid orange 10 has been investigated using Polyvinylpyrrolidone and Brij-35 stabilized iridium oxide nanoclusters as catalysts. Simple chemical reduction method was used to synthesize the above-mentioned nanoclusters. The characteristics of the nanocatalysts were determined by UV-visible spectrophotometer, TEM and XRD. The kinetic study has been carried out at λmax of reaction mixture i.e. 479 nm spectrophotometrically. The degradation follows first order kinetics with respect to oxidant and catalyst concentration while order is one at lower substrate concentration tending towards zero at higher concentration. The degradation kinetics has been supported by the derived rate law. The results showed that Polyvinylpyrrolidone stabilized iridium oxide nanoclusters outperformed Brij-35 stabilized iridium oxide nanoclusters, exhibiting the fastest degradation rate. The progress of the degradation process was monitored by UV-vis spectroscopy. Using Polyvinylpyrrolidone stabilized iridium oxide nanoclusters as a catalyst is a very promising approach for the remediation of acid orange 10 due to the fast degradation rate and high degradation efficiency. In addition, Polyvinylpyrrolidone stabilized iridium oxide nanoclusters can be easily recovered and recycled for three consecutive cycles. It can be inferred from this study that catalytic oxidation methods are active and environment-friendly for the remediation of dyes.